Pengaruh Persepsi Harga Terhadap Keputusan Pembelian Konsumen Lawson U-Town Bintaro - Nurwisesa; Muhammad Feby Andhika (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This research aims to determine the influence of price perception on purchasing decisions among Lawson consumers in U Town, Bintaro, South Tangerang City. The study employs a quantitative method using SPSS 25 software for hypothesis testing. The measurement instrument utilizes a Likert scale, requiring respondents to express the influence of service quality on their loyalty to using or purchasing Shell products. Data collection employs purposive sampling with a sample size of 120. The results of this research indicate that price perception has a positive influence on purchasing decisions among Lawson consumers in U Town, Bintaro, South Tangerang City.